Life is now! Time discounting and crime: evidence from the Italian regions (2002-2007) - Gilberto Turati
This paper tests the relationship between time preferences and crime rates as posited by Davis (1988), whose theoretical analysis suggests that individuals’ attitude towards the future significantly affect their propensity to commit crime. Our empirical analysis is based on a panel of Italian regions for the period 2002-2007. Various proxies for time preferences are considered: the consumer credit share out of the total amount of loans to households, the share of obese individuals out of the total population, and the rate of marriages out of the total population. In line with the theoretical prediction, our empirical analysis confirms that where people are more impatient and discount the future more heavily, property and violent crimes are higher. Results are robust to a number of alternative specifications including covariates drawn from the literature on the determinants of crime.Time Preferences, Property Crime, Violent Crime, Italian Regions, Panel data.